2022
DOI: 10.1177/15353702221090872
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the immune system to genitourinary fibrosis

Abstract: Fibrotic diseases of the genitourinary tract are devastating and incompletely understood pathologies. These diseases include urethral and ureteral strictures, retroperitoneal fibrosis, and Peyronie’s disease. They can contribute to obstructive uropathy and sexual dysfunction. Poor understanding of the pathophysiology of these diseases severely limits our ability to prevent and treat them. Genitourinary fibrotic diseases likely represent related pathologies that share common underlying mechanisms involving woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…As has been suggested by others, this pattern of focal fibrosis amongst a more widespread, organ-specific inflammatory effect, potentially implicates immune modulation rather than trauma as the cause. [16][17][18][19][20] The association of aUSD with systemic inflammation was evaluated in Aim 3 of the study, which hypothesized that higher levels of circulating inflammatory cytokines would be found in patients with inflammatory strictures, drawing upon previous studies that showed an association between systemic inflammatory conditions (eg, metabolic syndrome, diabetes) and inflammatory aUSD. 17 Cytokines are small proteins secreted by immune cells and the epithelium and are important in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been suggested by others, this pattern of focal fibrosis amongst a more widespread, organ-specific inflammatory effect, potentially implicates immune modulation rather than trauma as the cause. [16][17][18][19][20] The association of aUSD with systemic inflammation was evaluated in Aim 3 of the study, which hypothesized that higher levels of circulating inflammatory cytokines would be found in patients with inflammatory strictures, drawing upon previous studies that showed an association between systemic inflammatory conditions (eg, metabolic syndrome, diabetes) and inflammatory aUSD. 17 Cytokines are small proteins secreted by immune cells and the epithelium and are important in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 141 men with stricture enrolled in the study, of which 120 had both histopathologic and serum samples adequate for analysis. Additional men had tissue (18) or serum (3) only and were included in the analyses when appropriate. Patient demographics and basic stricture characteristics are shown in Table 1 and Supplemental Figure 1 (https://www.jurology.com).…”
Section: Cohort Demographicsmentioning
confidence: 99%
“…It is noteworthy that ureteral strictures, retroperitoneal fibrosis and PD are characterized by extracellular matrix abnormalities, such as collagen deposition, transforming growth factor-β accumulation, and dysregulation of collagen maturation-leading to abnormal tissue stiffness. Consequently, they share a systemic pro-inflammatory state likely contributing to their associated fibrogenesis [ 33 ]. To our knowledge, this is the first study to explore the role of NER and ENR as a potential biomarker associated with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this multi-layer burden, was the difficulty of the fistula repairs in the cases presented, owing in large part to the intra- and retroperitoneal fibrosis. We postulate the dissection performed during the index surgery induces fibrosis that is worsened by a systemic pro-inflammatory state induced by HIV and cancer as described by Doersch et al (2022) .…”
Section: Discussionmentioning
confidence: 99%